2019
DOI: 10.1111/njb.02314
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the chlorophyll content of grape leaves could provide a physiological index for responses and adaptation to UV‐C radiation

Abstract: Stilbenes are a group of phytoalexins that play an important role in grapevine (Vitis) basal immunity and can be induced by biotic and abiotic stresses. The levels of chlorophylls, the main pigments in plant cells, can also indicate the tolerance of plants to various stresses. Here, the response of different grapevine genotypes to UV‐C radiation treatment was tested and the abundance of chlorophyll in the Hoe29 and Ke53 genotypes was observed to increase significantly within 6 h of UV‐C treatment. Conversely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 73 publications
4
5
0
Order By: Relevance
“…However, MDA amount of UV-C-treated G4 was about 3.5 times that of the control group indicating that an oxidative imbalance took place following UV exposure in A. cepa roots. Our results were in accordance with the data of Luo et al ( 2019 ) who revealed that UV-C administration triggered a remarkable induction in MDA levels in grape leaves. Another study on Nicotiana tabacum callus showed that 254-nm UV radiation caused a remarkable increase in MDA accumulation from the 6 th hour of application (Zacchini and de Agazio 2004 ).…”
Section: Resultssupporting
confidence: 94%
“…However, MDA amount of UV-C-treated G4 was about 3.5 times that of the control group indicating that an oxidative imbalance took place following UV exposure in A. cepa roots. Our results were in accordance with the data of Luo et al ( 2019 ) who revealed that UV-C administration triggered a remarkable induction in MDA levels in grape leaves. Another study on Nicotiana tabacum callus showed that 254-nm UV radiation caused a remarkable increase in MDA accumulation from the 6 th hour of application (Zacchini and de Agazio 2004 ).…”
Section: Resultssupporting
confidence: 94%
“…In our study, much greater increase in MDA content in the 254 nm UV-treated group compared to the 365 nm UV-treated group indicated that UV-C caused a more serious oxidative burst in Allium root cells. Similar to our results,Luo et al (2019) reported a remarkable increase in MDA levels in UV-C radiation-exposed grapes. In another study, UV-C pulses triggered signi cant increases in MDA contents of tobacco callus in a time-dependent manner(Zacchini and de Agazio 2004).…”
supporting
confidence: 92%
“…According toUrban et al (2016), lipid peroxidation is one of the direct effects of ionizing radiation in plants. As a cytotoxic material, MDA points out both the degree of lipid peroxidation in biological membranes caused by the over-production of reactive oxygen species (ROS) and the e ciency of the stress defense(Skórzyńska 2007;Luo et al 2019). In our study, much greater increase in MDA content in the 254 nm UV-treated group compared to the 365 nm UV-treated group indicated that UV-C caused a more serious oxidative burst in Allium root cells.…”
mentioning
confidence: 99%
“…However, excessive light conditions bare the risk of damaging proteins and the light harvesting pigments of the photosynthetic system [73]. High irradiation of leaf tissue results in significantly lower leaf chlorophyll content compared to shaded leaves [74,75], which was also confirmed for exposed canopies in this study (Figure 4). Suggested optimum values for leaf Chl i content were seldom reached by the different canopy sites of the examined steep slope management systems [31].…”
Section: Leaf Nitrogensupporting
confidence: 78%